Postgraduate writing groups as spaces of agency development - Oluwole, D.O.; Achadu, O.; Asfour, F.; Chakona, G.; Mason, P.; Mataruse, P.; McKenna, S. (South African Journal of Higher Education, 2018)
Abstract Academic writing is a peculiar phenomenon – it varies greatly from discipline to discipline and its requirements are rarely made overt. Taking on the writing practices of the academy has implications for identity and it is thus unsurprising that it is seen to be a risky endeavour. This article analyses the experiences of postgraduate scholars who have participated in writing groups that meet weekly to read each other’s work and provide supportive critique. Thirty-two people provided detailed, anonymous evaluations of their writing groups and these were analysed using a discourse analysis. Three main findings are discussed here. Firstly, writing circles allowed for academic writing development to be engaged with as a social practice, where the disciplinary norms could be made more explicit through peer deliberation, and where they could also be challenged. Secondly, the lack of hierarchical power in the writing groups was key to making safe spaces for agency development, and also for providing positive peer pressure whereby participants were spurred on to work on their writing. Thirdly, the fact that the groups were interdisciplinary, within cognate disciplinary families, provided an interesting challenge in that the students had to consider what these non-specialist readers would or would not understand. This process assisted students in clarifying their writing. Participants’ evaluation of the writing groups revealed an overall sense that these contributed to postgraduate student wellbeing and were places of significant agential development.